Effect of Training Method and Spraying Gibberellic and Salicylic Acid on Some Flowers Characters of Snapdragon Plants Antirrhinum majus L. - Ali, Yaemur Ahmed; Al- Sheikhli, Abdulrahman Abdulqader (Journal of agricultural, environmental and veterinary sciences, 2019)
The experiment was conducted at research station of the Horticulture and landscape department/ Agriculture college/ Diyala university during 2017- 2018 seasons (8/10/2017- 4/5/2018). The objectives of the experiment were to investigate the effect of training method , training method included four types (single stem, double stems , three stems and four stems). Gibberellic acid sprayed with two concentration (100 , 200 mg.L- 1) also salicylic acid sprayed with two concentration (50, 100 mg.L- 1) and control treatment sprayed two times with distilled water in 15/1/2018 and 15/2/2018.Training methods had significant effects on floral growth characteristics, Single- stem training method had the best regarding days number for inflorescence emergence 131.44days, inflorescence length 44.87cm, inflorescence diameter13.39cm, florets number on inflorescence 46.01 Floret/spike, flowering stem length 86.59cm, flowering stem diameter 10.20mm and petals anthocyanins content 28.30mg/l dry weight. give spraying 100 mg/l of gibberellic acid had best results regarding inflorescence length 44.88cm, inflorescence diameter 13.26cm, florets number on inflorescence 50.47 floret/spike, flowering stem length 81.64cm, flowering stem diameter 10.88mm. give spraying 100 mg/l of Salicylic acid had best results regarding days number for inflorescence emergence 132.66days and petals anthocyanins content 28.65 mg/l dry weight. Interactions between the studied factors had significant effect in all studied characteristics.
Keywords: Snapdragon Plant; Gibberellic; Salicylic; spray leaf's